The Effect of Water Soaking, Enzyme Supplementation and Microwave Treatment on The Nutritive Value of Rice Bran for Broiler Chicken - N. G. A. Mulyantini; Ulrikus R. Lole (Faculty of Animal Science, Universitas Gadjah Mada, 2000)
Artikel dalam bentuk PDF